STRATEGI PEMASARAN DENGAN MENGGUNAKAN ANALISIS SWOT (Studi pada Toko Cahaya Baru Collection di Pasar Kuok) - Marzalina Marzalina; Henny Indrawati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to analyze the strengths, weaknesses, opportunities and threats, and also to determine the right marketing strategy in Cahaya Baru Collection Store. The unit of analysis in this study is Cahaya Baru Collection Store. Data collection techniques using field research, data obtained by interview and questionnaire. The data analysis technique used is the analysis of IFE and EFE matrices, IE matrices and SWOT matrices. The results of this study indicate that the results of the IFE matrix analysis of the total score of 2.94 which is the main strength is good quality and product quality, a choice of models / products that are complete and give a price discount of 10%, while the main weakness is the less than optimal promotion. The EFE matrix analysis results in a total score of 2.98 which is the main opportunity is consumer purchasing power that tends to be consumptive, the need for a religious new year and the existence of consumer loyalty, while the threat is the high level of competition and fluctuating people's income. The result of IE matrix shows that the position of the Cahaya Baru Collection Store is in the position of cell V (hold and maintain). The results of the SWOT matrix analysis have 7 alternative strategies, namely: maintaining product quality and choice of complete models / products, maintaining good relations with supplier and consumers, increasing competitiveness of competitors, maintaining a 10% discount on every product unit sold, expanding market share to increase sales volume, supply more product sizes, sell types of products that suit consumers' tastes.Key Words: Marketing Strategy, SWOT Analysis